I have a coupled non-dimensional diffusion system in $v(z,\tau)$, formulated by the following equations

\begin{align} \frac{\partial v}{\partial \tau} &= \Delta\frac{\partial^2 v}{\partial z^2}, % \qquad &\text{for}\ z\in[0,1],\ \tau>0 \\ %%% \frac{\partial v}{\partial z} &= Ev, % \qquad &\text{for}\ z=0,\ \tau>0,\\ %%% \frac{\partial v}{\partial z} &= -D v, % \qquad &\text{for}\ z=1,\ \tau>0 \end{align}

where $\Delta,E,D>0$

We next proceed with separation of variables, let \begin{align} v = Z(z)T(\tau) \end{align}

Substitution yields the following \begin{align} \frac{1}{\Delta}\frac{\dot{T}}{T} &= \frac{Z''}{Z} = -\lambda^2 \end{align}

Therefore we find \begin{align} T &\propto \exp{\left(-\Delta\lambda^2\tau\right)},\\ Z &= a \cos(\lambda z) + b\sin(\lambda z),\\ Z' &= \lambda \left( b\cos(\lambda z) -a \sin(\lambda z) \right) \end{align}

WLOG we may set $a=1$, as we will later take a linear superposition of these solution functions. Therefore we have \begin{align} Z &= \cos(\lambda z) + b\sin(\lambda z),\\ Z' &= \lambda \left( b\cos(\lambda z) - \sin(\lambda z) \right) \end{align}

Therefore via our boundary condition at $z=0$ we find \begin{align} \lambda b &= E \quad\Rightarrow\quad b = \frac{E}{\lambda} \end{align}

and via our second \begin{align} \lambda \left( \frac{E}{\lambda}\cos(\lambda) - \sin(\lambda) \right) &= -D\left(\cos(\lambda) + \frac{E}{\lambda}\sin(\lambda)\right)\\ %%% \Rightarrow\quad E\lambda\cos(\lambda) - \lambda^2\sin(\lambda) &= -D\cos(\lambda) - ED\sin(\lambda)\\ %%% \Rightarrow\quad \left(E\lambda+D\right)\cos(\lambda) &= \left( \lambda^2- ED\right)\sin(\lambda)\\ %%% \Rightarrow\quad \tan(\lambda) &= \frac{E\lambda+D}{\lambda^2- ED} \end{align}

This has countably infinite solutions $\lambda_i$ for $i\in\mathbb{N}$. Therefore we have the following solution for $v(z,\tau)$ \begin{align} v(z,\tau) &= \sum_{i=1}^\infty C_n \left( \cos(\lambda_i z) + \left(\frac{E}{\lambda_i}\right)\sin(\lambda_i z) \right) \exp{\left(-\Delta\lambda_i^2\tau\right)} \end{align}

Therefore at $\tau=0$ \begin{align} v(z,0) &= \sum_{i=1}^\infty C_i \left( \cos(\lambda_i z) + \left(\frac{E}{\lambda_i}\right)\sin(\lambda_i z) \right) = 1 \end{align}

How can I find $C_i$?.

EDIT: If we define $Z_i(z)$ as follows \begin{align} Z_i(z) = \cos(\lambda_i z) + \left(\frac{E}{\lambda_i}\right)\sin(\lambda_i z) \end{align}

then am I correct in thinking we use the following relation to find $C_i$? \begin{align} \int_0^1 Z_i(z)Z_j(z) \text{d}z = c_i\delta_{ij} \end{align}

I'm not sure if this is the case, see this link. Does this mean my spatial basis is not orthogonal?

  • $\begingroup$ I'm confused. Are the last four equations boundary conditions? i.e $$\frac{\partial u}{\partial z} = Az \quad \text{for $z = -\delta$} \implies \frac{\partial u(-\delta, \tau)}{\partial z} = Az$$ $\endgroup$ – mattos Jan 16 '18 at 14:13
  • $\begingroup$ @Mattos: You are correct, those are boundary conditions. $\endgroup$ – Freeman Jan 16 '18 at 14:17
  • $\begingroup$ Just for completeness, how do you know, $v(z,0)=1$? Do you have an initial condition for $v$? I guess so... $\endgroup$ – Andras Vanyolos Mar 13 '19 at 21:32

The equation in $Z$ is $$ -Z'' = \lambda^2 Z, \\ Z'(0)-EZ(0)=0 \\ Z'(1)+DZ(1)=0. $$ If $Z_1$ is a solution for $\lambda_1$ and $Z_2$ is a solution for $\lambda_2$, then \begin{align} (\lambda_2^2-\lambda_1^2)\int_{0}^{1}Z_1(z)Z_2(z)dz & = \int_{0}^{1}Z_1Z_2''-Z_1''Z_2 dz \\ & = \int_{0}^{1}\frac{d}{dz}(Z_1Z_2'-Z_1'Z_2)dz \\ & = Z_1Z_2'-Z_1'Z_2|_{0}^{1} \\ & = \left.\left|\begin{array}{cc}Z_1 & Z_2 \\ Z_1' & Z_2'\end{array}\right|\right|_{0}^{1} = 0. \end{align} The determinants at $0$ and at $1$ are individually $0$ because the matrices have non-trivial null spaces: $$ \left[\begin{array}{cc} Z_1(0) & Z_1'(0) \\ Z_2(0) & Z_2'(0)\end{array}\right]\left[\begin{array}{c}1 \\ -E\end{array}\right] = 0, \\ \left[\begin{array}{cc} Z_1(1) & Z_1'(1) \\ Z_2(1) & Z_2'(1)\end{array}\right]\left[\begin{array}{c}1 \\ \;\;D\end{array}\right] = 0. $$ Therefore, if $\lambda_1\ne\lambda_2$, $$ \int_{0}^{1}Z_1(z)Z_2(z)dz = 0. $$

| cite | improve this answer | |
  • $\begingroup$ Thank you! This is a really helpful explanation! How do I go from here to find $C_i$? $\endgroup$ – Freeman Jan 22 '18 at 9:11
  • $\begingroup$ @Freeman : You'll just have to brute force the trig integrals, and everything will end up depending on the $\lambda_i$, which are solutions of a transcendental equation. You'll probably be able to simplify the final expressions somewhat by using the form of the transcendental equations for the $\lambda_i$. But that's about all you can do. $\endgroup$ – Disintegrating By Parts Jan 22 '18 at 16:05
  • $\begingroup$ Thank you! I just got this working :) $\endgroup$ – Freeman Jan 22 '18 at 16:14
  • $\begingroup$ @Freeman : You're welcome. :) $\endgroup$ – Disintegrating By Parts Jan 22 '18 at 17:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.